The Effect of Current and Time on Nut Spot Welding Process Towards Torque Test in Export Crate Construction - Subroto, Hadi; Muslimin, M.; Tjahyono, Seto (PT Mattawang Mediatama Solution, 2022)
The problem of loose spot welding nuts during knockdown is a problem, from the cost of replacing the loose spot welding nut and additional time to repair damage that can reduce productivity. To increase the strength of spot welding, it is necessary to test with certain variables, namely the spot welding process with five variables 25A, 30A, 40A, 50A, and 60A, five time variables 0.5 seconds, 1.0 seconds, 1.5 seconds, 2.0 seconds and 2.5 seconds. Each of 30 samples of each variable were tested for destructive torque with a digital torque wrench to get a precise torque value and SEM photos to determine the HAZ of the spot welding process. The results obtained from this study are to determine the effective value of each variable so as to increase the efficiency of repair costs in terms of goods and time due to the release of nut spot welding. Tests are carried out to increase productivity in terms of time and cost efficiency as well as to find out the science in examining the effect of current and time variables in the spot welding process.